Strategi Kedekatan Emosional Host Live Lozy Hijab di TikTok: Analisis Gaya Komunikasi Panggilan ‘Beb, Sayang, Cinta’ dan Loyalitas Konsumen - Nadhila Zulfa Khairani; Tsania Nurizka Larasati (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The phenomenon of using emotional greetings such as “beb,” “sayang,” and “cinta” by the host of Lozy Hijab's live stream on TikTok reflects interpersonal communication practices that are deliberately constructed to create closeness with the audience. This communication style is evident in the choice of words, intonation, expressions, and the host's responses to audience comments, resulting in a friendly, warm, and personal atmosphere of interaction. The approach used is a qualitative method with a focus on case studies to analyze the emotional closeness strategy of the Lozy Hijab live host with the communication style of “beb, sayang, cinta” and consumer loyalty. Data was collected through interviews, observation, and documentation, with in-depth interviews applied in the research being conducted by the researcher. The data analysis methods used included data reduction, comprehension, and interpretation. In addition, the data was also validated through the use of technique triangulation and source triangulation. The results of this study show that the use of emotional greetings such as “beb,” “sayang,” and “cinta” is not just a spontaneous communication style, but has developed into an emotional closeness strategy that serves to build interpersonal relationships between live hosts and viewers. The emotional communication style used by Lozy Hijab hosts not only builds closeness, but also has a direct impact on consumer loyalty and increased sales.